ROLE OF EMPLOYEE ENGAGEMENT ON WORK SATISFACTION REGARDING EMPLOYEE SERVICES QUALITY AT THE GRAND SANTHI HOTEL DENPASAR - Puspitawati, Ni Made Dwi; Yuliawan, Adhi Krisna (Review of Management and Entrepreneurship, 2019)
The hotel is one of the facilities that strongly supports the progress of the tourism sector. Problems most commonly occur in regards to the lack of service quality are due to complaints received and employees who do not understand their functions and tasks clearly. Job satisfaction could be related to this lack of service that in turn affects the level of company engagement. The study examines the role of employee engagement on the relationship between work satisfaction and service quality. Results using path analysis show that work satisfaction influences employee engagement and service quality; and employee engagement influences service quality. Thus, proving that a high level of satisfaction will result in a higher sense of employee attachment to companies, which will create quality services.